Light-emitting element
Patent Information
- Application Number
- JP2023126475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0012】 上記態様によれば、p側電極はMgまたはMgを主成分とする合金からなり、p型層に直接接触している。そのため、p型層に対して良好なコンタクトを取りつつ、UVC帯の反射率が高いp側電極を実現することができる。
Smart Images

Figure 2025022162000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a light-emitting device. [Background technology]
[0002] The wavelength of ultraviolet light emitted by solid-state light-emitting devices using III-nitride semiconductors corresponds to a wavelength band of approximately 210 to 400 nm. UVC (wavelength 100 to 280 nm) is known to be effective for sterilization and disinfection, and is attracting attention for its use in sterilizing and disinfecting water and air. As a result, there is a growing demand for III-nitride semiconductor light-emitting devices that emit ultraviolet light with an emission wavelength corresponding to UVC, and research and development aimed at improving efficiency is being actively conducted.
[0003] UV light-emitting devices using III-nitride semiconductors are of the flip-chip type, which extracts light from the back side of the substrate. In such flip-chip devices, it is conceivable to improve the light extraction efficiency by increasing the reflectivity of the p-side electrode and having the p-side electrode reflect UV light to the light extraction side.
[0004] Patent Document 1 shows a structure in which a Ni layer and an Mg layer are laminated in this order from the p-type layer side as a p-side electrode of an ultraviolet light-emitting element using a group III nitride semiconductor. The Ni layer is a layer for making good contact with the p-type layer, and the Mg layer is a layer for reflecting ultraviolet light in the UVC band. In the UVC band, Mg has a higher reflectance than Al. Therefore, Patent Document 1 aims to improve the reflectance by using Mg as the reflective layer of the p-side electrode.
[0005] Furthermore, Patent Document 2 describes a Group III nitride semiconductor light-emitting device that emits light with a wavelength of 300 nm or less, and describes the use of a transparent electrode made of Mg as the positive electrode in contact with the p-type layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-36629 A [Patent Document 2] JP 2014-96539 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, the Ni / Mg described in Patent Document 1 may have a lower external quantum efficiency EQE than Ni / Al. This is thought to be because Ni / Mg needs to be optimized to achieve both improved reflectivity and reduced contact resistance, but this requires optimizing the Ni layer thickness and annealing conditions, which is difficult.
[0008] Furthermore, in Patent Document 2, Mg is thinned and used as a transparent electrode, but there is no mention of using it as a reflective electrode.
[0009] The present invention has been made in view of the above background, and aims to provide a light-emitting device having a p-side electrode with high reflectance. [Means for solving the problem]
[0010] One aspect of the present invention is A flip-chip type ultraviolet light emitting device having a p-type layer made of a p-type Group III nitride semiconductor and a p-side electrode which is a reflective electrode provided on the p-type layer, The p-side electrode is made of Mg or an alloy mainly composed of Mg, and is in contact with the p-type layer in the light emitting element.
[0011] Another aspect of the present invention is A method for manufacturing a flip-chip type ultraviolet light-emitting light-emitting device having a p-type layer made of a p-type Group III nitride semiconductor and a p-side electrode which is a reflective electrode provided on the p-type layer, comprising: a p-side electrode formation step of forming the p-side electrode made of Mg or an alloy mainly containing Mg on the p-type layer; The method for manufacturing a light emitting device further comprises an annealing step of performing annealing in an inert gas atmosphere at a temperature of 150° C. to 400° C. for 30 seconds to 12 minutes after the formation of the p-side electrode. Effect of the Invention
[0012] According to the above embodiment, the p-side electrode is made of Mg or an alloy mainly composed of Mg and is in direct contact with the p-type layer, which makes it possible to realize a p-side electrode with high reflectance in the UVC band while maintaining good contact with the p-type layer. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing the configuration of a light-emitting device in embodiment 1, taken along a direction perpendicular to a main surface of a substrate. [Diagram 2] FIG. 2 is a diagram showing a manufacturing configuration of the light-emitting device according to the first embodiment. [Diagram 3] A graph showing the relationship between the thickness of the Mg layer and the relative reflectance. [Figure 4] 1 is a graph showing the current dependence of the optical output Po for the light-emitting elements of Example 1 and Comparative Examples 1 and 2. [Diagram 5] 1 is a graph showing the current dependence of external quantum efficiency EQE for the light-emitting elements of Example 1 and Comparative Examples 1 and 2. [Figure 6] 4 is a graph showing IV characteristics of the light-emitting elements of Example 1 and Comparative Examples 1 and 2. [Figure 7] 4 is a graph showing the power conversion efficiency WPE of the light-emitting elements of Example 1 and Comparative Examples 1 and 2. [Figure 8] 1 is a graph showing the relationship between the wavelength of ultraviolet light and relative reflectance. [Figure 9] A micrograph of the p-side electrode. [Figure 10] 1 is a graph showing IV characteristics before and after annealing. [Figure 11] Graph showing emission spectra before and after annealing. [Figure 12] Graph showing the change in annealing temperature over time. [Figure 13] 1 is a graph showing the relationship between the annealing temperature and the amount of Vf reduction. [Figure 14] Graph showing the relationship between annealing temperature and change in reflectance of Mg / Ti. [Figure 15] Graph showing the change in annealing temperature over time. [Figure 16] 1 is a graph showing the relationship between annealing time and the amount of Vf reduction. [Figure 17] Graph showing the relationship between annealing time and the amount of change in reflectance of Mg / Ti. [Figure 18] 4 is a graph showing the relationship between the optical output Po and current of the light-emitting element of Example 1. [Figure 19] 4 is a graph showing IV characteristics of the light-emitting element of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The light-emitting element has a p-type layer made of a p-type Group III nitride semiconductor, and a p-side electrode which is a reflective electrode provided on the p-type layer, and in the flip-chip type ultraviolet-emitting light-emitting element, the p-side electrode is made of Mg or an alloy mainly composed of Mg and is in contact with the p-type layer.
[0015] The thickness of the p-side electrode may be set so that the reflectance at the emission wavelength is 50% or more.
[0016] The thickness of the p-side electrode may be 40 nm or more. Furthermore, the thickness of the p-side electrode may be 80 nm or more.
[0017] The semiconductor device may further include a protective layer that is provided on and in contact with the p-side electrode and is made of Ti, TiN, or Ni.
[0018] The emission wavelength of the light emitting element may be 210 to 280 nm.
[0019] A method for manufacturing an ultraviolet-emitting light-emitting element having a p-type layer made of a p-type Group III nitride semiconductor and a p-side electrode which is a reflective electrode provided on the p-type layer, includes a p-side electrode formation step of forming a p-side electrode made of Mg or an alloy mainly composed of Mg in contact with the p-type layer, and an annealing step of annealing, after the formation of the p-side electrode, in an inert gas atmosphere at a temperature of 150° C. or more and 400° C. or less for 30 seconds to 12 minutes.
[0020] The annealing temperature in the annealing step may be 200° C. or more and 350° C. or less. The annealing time in the annealing step may be 2 minutes or more and 8 minutes or less.
[0021] In the p-side electrode forming step, the p-side electrode may be formed to have a thickness of 40 nm or more. Also, in the p-side electrode forming step, the p-side electrode may be formed to have a thickness of 80 nm or more.
[0022] The p-side electrode formation step may include a step of forming a protective layer made of Ti, TiN, or Ni on and in contact with the p-side electrode.
[0023] In the above-mentioned method for producing a light-emitting device, the light-emitting device may have an emission wavelength of 210 to 280 nm.
[0024] (Embodiment 1) Fig. 1 is a cross-sectional view showing the configuration of the light-emitting element in embodiment 1, and shows a cross section in a direction perpendicular to the main surface of the substrate. As shown in Fig. 1, the light-emitting element in embodiment 1 has a substrate 10, an n-type layer 11, an active layer 12, an electron blocking layer 13, a composition gradient layer 14, a p-type contact layer 15, an n-side electrode 16, and a p-side electrode 17. The light-emitting element in embodiment 1 is a flip-chip type that extracts light from the back surface of the substrate 10 (the surface opposite to the n-type layer 11). The emission wavelength is a predetermined wavelength in the range of 210 to 280 nm, and is in the UVC band (100 to 280 nm).
[0025] 1. Light-emitting element configuration The configuration of each layer of the light-emitting device in embodiment 1 will be described in detail.
[0026] The substrate 10 is a substrate made of sapphire with a c-plane as the principal surface. The plane orientation of the principal surface of the sapphire may be the a-plane. In addition, the substrate may have an off angle of 0.1 to 2 degrees in the m-axis direction. The back surface of the substrate 10 (the surface opposite to the n-type layer 11) serves as the main light extraction surface. An anti-reflection film may be provided on the back surface of the substrate 10 to improve the light extraction efficiency. In addition, the surface of the substrate 10 may be provided with irregularities to improve the light extraction efficiency. In addition, an AlN substrate or an AlN template substrate in which an AlN layer is formed on a sapphire substrate may be used as the substrate 10.
[0027] The thickness of the substrate 10 is, for example, 1000 μm or less, and preferably 300 μm or more and 500 μm or less, which can suppress light extraction from the side surface of the substrate 10 and improve on-axis intensity.
[0028] The substrate 10 may be removed by a method such as LLO (laser lift-off).
[0029] The n-type layer 11 is located on the substrate 10. The n-type layer 11 is made of n-AlGaN. The Al composition (the molar ratio of Al in the whole group III metals) is, for example, 60 to 90%. The n-type impurity is Si, and the Si concentration is, for example, 1×10 18 ~5×10 19 cm -3 The thickness of the n-type layer 11 is, for example, 0.5 to 5 μm. The C concentration of the n-type layer 11 is 1×10 15 ~1×10 19 cm -3 The n-type layer 11 may be composed of a plurality of layers. For example, it may be a superlattice layer in which AlGaN layers having different Al compositions are alternately stacked. Also, an underlayer made of AlN may be provided between the substrate 10 and the n-type layer 11. Also, an element other than Si may be used as the n-type impurity.
[0030] The active layer 12 is located on the n-type layer 11. The active layer 12 has an SQW structure in which a barrier layer, a well layer, and a barrier layer are stacked in this order from the n-type layer 11 side. The active layer 12 may have an MQW structure. In that case, the number of repetitions is, for example, 2 to 10.
[0031] The well layer is made of AlGaN, and the Al composition is set according to the desired emission wavelength. The Si concentration in the well layer is, for example, 1×10 18 cm -3 The well layer may be non-doped and has a thickness of, for example, 0.5 to 5 nm.
[0032] The barrier layer is made of AlGaN having a larger Al composition than the well layer, and the Al composition is, for example, 50 to 100%. The Si concentration of the barrier layer is, for example, 2×10 19 cm -3 or less, and may be non-doped. The thickness of the barrier layer is, for example, 3 to 30 nm. The barrier layer may be made of AlGaInN, which has a larger band gap energy than the well layer. Furthermore, the layer of the barrier layer in contact with the electron blocking layer 13 preferably has a thickness of 0.5 to 10 nm.
[0033] A hole blocking layer may be provided between the n-type layer 11 and the active layer 12. This can prevent holes injected from the p-side electrode 17 from diffusing beyond the active layer 12 toward the n-type layer 11. The hole blocking layer is made of AlGaN or AlN having a higher Al composition than the barrier layer of the active layer 12. The thickness of the hole blocking layer is, for example, one molecular layer to 2 nm. In the case of AlN, one molecular layer is approximately 0.26 nm.
[0034] The electron blocking layer 13 is located on the active layer 12. The electron blocking layer 13 has a two-layer structure in which a first electron blocking layer and a second electron blocking layer are laminated in this order from the active layer 12 side. The electron blocking layer 13 prevents electrons injected from the n-side electrode 16 from diffusing beyond the active layer 12 toward the composition gradient layer 14 side.
[0035] The electron blocking layer 13 does not necessarily have to have a two-layer structure, and may consist of only a first electron blocking layer.
[0036] The first electron blocking layer is made of AlGaN or AlN having a higher Al composition ratio than the barrier layer of the active layer 12, and the Al composition is, for example, 90 to 100%. The first electron blocking layer may be doped with a p-type impurity or may be undoped. The p-type impurity is, for example, Mg. When doped with Mg, the Mg concentration is, for example, 3×10 20 cm -3 The thickness of the first electron blocking layer is, for example, 1 to 10 nm.
[0037] The second electron blocking layer is made of AlGaN having a lower Al composition than the first electron blocking layer, and the Al composition is, for example, 80 to 99%. By providing the second electron blocking layer, the difference in Al composition with the composition gradient layer 14 is adjusted. If the first electron blocking layer is made of AlN alone, the resistance will be high, and if the first electron blocking layer is made thin, the electron blocking performance will decrease. Therefore, by providing the second electron blocking layer, both low resistance and electron blocking function are achieved. The second electron blocking layer may be doped with p-type impurities or may be undoped. In the case of Mg doping, the Mg concentration is, for example, 3×10 20 cm -3 The second electron blocking layer has a thickness of, for example, 1 to 10 nm.
[0038] The compositionally graded layer 14 is located on the electron blocking layer 13. The compositionally graded layer 14 has a two-layer structure in which a first compositionally graded layer and a second compositionally graded layer are laminated in this order from the electron blocking layer 13 side.
[0039] The compositionally graded layer 14 is a layer that has been made p-type by a method called polarization doping. That is, the compositionally graded layer 14 is a layer in which the Al composition changes in the thickness direction, and is set so that the Al composition decreases with increasing distance from the electron blocking layer 13. It was difficult to increase the hole concentration of AlGaN with a high Al composition by Mg doping, but polarization doping can improve the hole concentration and increase the efficiency of hole injection into the active layer 12. In addition, polarization doping does not require Mg doping, so crystallinity can be improved.
[0040] When the Al composition of the compositionally graded layer 14 is set as described above, polarization due to crystal distortion occurs continuously in the compositionally graded layer 14 in the thickness direction. Holes are generated in the compositionally graded layer 14 to cancel the fixed charges caused by this polarization. The generated holes are distributed in the compositionally graded layer 14. Therefore, the holes are widely distributed in the thickness direction from the electron block layer 13 side in the compositionally graded layer 14, and the layer as a whole becomes p-type. In this p-type region, the hole concentration is 1×10 16 ~1×10 20 cm -3 The hole concentration decreases with increasing distance from the electron blocking layer 13. The reason why the number of holes decreases near the interface of the compositionally graded layer 14 with the p-type contact layer 15 is that the Fermi levels attempt to match due to the p-type heterojunction, causing the band to bend.
[0041] The maximum value of the Al composition of the first composition gradient layer (the Al composition at the interface with the electron blocking layer 13) is preferably 1 to 20% lower than the Al composition of the electron blocking layer 13. The hole concentration can be further increased by polarization due to strain. For example, the maximum value of the Al composition is 65 to 95%.
[0042] In addition, the minimum value of the Al composition of the first composition gradient layer (the Al composition at the interface with the second composition gradient layer) is preferably 3 to 30% lower than the maximum value of the Al composition of the first composition gradient layer. The hole concentration can be further increased by polarization due to strain. In addition, the Al composition is preferably one having a band energy that does not absorb the emission wavelength.
[0043] The decrease rate of the Al composition of the first composition gradient layer is preferably 0.1 to 0.3% / nm. By setting the decrease rate in this range, the hole concentration of the first composition gradient layer can be further increased. The decrease rate of the Al composition may be constant, that is, may change linearly, or may not be constant.
[0044] The first composition gradient layer is undoped. However, it may be doped with Mg. This is expected to further increase the hole concentration by the p-type impurity. In this case, the Mg concentration is, for example, 1×10 20 cm -3 On the other hand, from the viewpoint of suppressing a change in series resistance due to a change in the thickness of the first composition gradient layer, it is preferable that the Mg concentration is as low as possible, and it is preferable that the first composition gradient layer is not doped.
[0045] The second compositional gradient layer is a layer having a higher Mg concentration than the first compositional gradient layer, and the other portions have the same Al composition as the first compositional gradient layer. That is, the Al composition changes in the thickness direction, and the Al composition decreases with increasing distance from the electron block layer 13. Doping the second compositional gradient layer with Mg enables good connection to the p-type contact layer 15.
[0046] The difference between the maximum value of the Al composition of the second composition gradient layer (the Al composition at the interface with the first composition gradient layer) and the minimum value of the Al composition of the first composition gradient layer is 0 to 5%, and is preferably the same as the minimum value of the Al composition of the first composition gradient layer. In other words, it is preferable that the Al composition is continuous from the first composition gradient layer to the second composition gradient layer.
[0047] Moreover, the minimum value of the Al composition of the second composition gradient layer (the Al composition at the interface with the p-type contact layer 15) is preferably 3 to 30% lower than the maximum value of the Al composition of the second composition gradient layer.
[0048] The decrease rate of the Al composition of the second composition gradient layer is in the same range as the decrease rate of the Al composition of the first composition gradient layer, and may be the same as the decrease rate of the Al composition of the first composition gradient layer.
[0049] The Mg concentration of the second composition gradient layer is arbitrary as long as it is higher than the Mg concentration of the first composition gradient layer. 20 cm -3 It is preferable that the number of the electrodes is less than or equal to 100 in order to suppress the series resistance.
[0050] In the first embodiment, the Al composition of the composition gradient layer 14 decreases continuously, but it may decrease stepwise. However, it is preferable that the region where the Al composition is constant is as small as possible.
[0051] The thickness ratio of the first composition gradient layer to the composition gradient layer 14 is preferably 0.4 to 0.7. This range ensures sufficient improvement in hole concentration by polarization doping while also providing good contact between the composition gradient layer 14 and the p-type contact layer 15. The thickness ratio is more preferably 0.4 to 0.6.
[0052] The composition gradient layer 14 does not necessarily have to have a two-layer structure of the first composition gradient layer and the second composition gradient layer, but may have only the first composition gradient layer. Also, it may have a structure of three or more layers with different Al composition change rates, Mg concentrations, etc.
[0053] The ratio of the thickness of the composition gradient layer 14 to the total thickness of the electron block layer 13, the composition gradient layer 14, and the p-type contact layer 15 is preferably 50% or more and 90% or less. Within this range, the function as a p-type layer can be sufficiently enhanced.
[0054] Instead of the compositionally graded layer 14, a layer made of Mg-doped p-type AlGaN may be provided. In this case, the Mg concentration is, for example, 1×10 17 ~1×10 19 cm -3 The Al composition is, for example, 40 to 80%.
[0055] The p-type contact layer 15 is located on the compositionally graded layer 14. The p-type contact layer 15 is made of Mg-doped p-GaN. It may be p-AlGaN having a lower Al composition than the minimum Al composition of the compositionally graded layer 14, for example, the Al composition is 50% or less.
[0056] The thickness of the p-type contact layer 15 is preferably, for example, one molecular layer or more and 50 nm or less. GaN absorbs the ultraviolet light emitted from the active layer 12, but by making it sufficiently thin, it is possible to transmit the ultraviolet light. Therefore, a large decrease in the external quantum efficiency can be avoided. The thickness is preferably 1 nm or more and 10 nm or less. The Mg concentration of the p-type contact layer 15 is, for example, 1×10 20 ~1×10 22 cm -3 It is.
[0057] The p-type contact layer 15 may be composed of multiple layers with different Al compositions or Mg concentrations. If composed of multiple layers, the top layer in contact with the p-side electrode 17 is preferably p-GaN or AlGaN with a low Al composition in order to reduce the contact resistance of the p-side electrode 17.
[0058] A groove is provided in a partial area of the surface of the p-type contact layer 15, the depth of which reaches the n-type layer 11. This groove is for exposing the n-type layer 11 so that an n-side electrode 16 can be provided therein.
[0059] The n-side electrode 16 is provided on the n-type layer 11 exposed at the bottom of the groove. The material of the n-side electrode 16 is Ti / Al, V / Al, etc. Here, A / B means that A and B are laminated in order from the n-type layer 11 side.
[0060] The p-side electrode 17 is provided on the p-type contact layer. The p-side electrode 17 is a reflective electrode that reflects ultraviolet light emitted from the active layer 12 toward the substrate 10 to increase light extraction efficiency. The p-side electrode 17 is made of Mg and is in contact with the p-type contact layer 15. Mg has a high reflectance for ultraviolet light, particularly in the UVC band, and can make good contact with the p-type Group III nitride semiconductor. Therefore, by using Mg as the p-side electrode 17, it is possible to increase the reflectance in the UVC band while making good contact with the p-type contact layer 15.
[0061] The thickness of the p-side electrode 17 is preferably set so that the reflectance of ultraviolet light of the emission wavelength is 50% or more. The reflectance here is the reflectance when ultraviolet light is input perpendicularly to the main surface of the p-side electrode 17. It is more preferably 70% or more, and further preferably 80% or more.
[0062] Moreover, the thickness of the p-side electrode 17 is preferably 40 nm or more. By making it 40 nm or more, it is possible to obtain a reflectance equal to or higher than that when Ni / Mg is used as the p-side electrode 17. It is more preferable that it is 80 nm or more. If it is 80 nm or more, it is possible to obtain a reflectance equal to or higher than that of Al. It is even more preferable that it is 90 nm or more. There is no particular upper limit for the thickness of the p-side electrode 17, but if it exceeds 80 nm, the reflectance gradually becomes saturated and the formation time and material costs are also increased, so it is preferable that it is 200 nm or less. It is more preferable that it is 160 nm or less.
[0063] The p-side electrode 17 may be made of an Mg alloy containing Mg as a main component instead of Mg. For example, an Mg-Al alloy, an Mg-Pt alloy, an Mg-Ni alloy, an Mg-Ni-Au alloy, etc. can be used. However, in order to improve reflectivity, the proportion of Mg in the alloy is preferably 70 at % or more.
[0064] The p-side electrode 17 may further include a protective layer made of Ti, located on and in contact with the p-side electrode 17. The protective layer protects the p-side electrode 17 from chemicals in the process after the formation of the p-side electrode 17, and protects the p-side electrode 17 from oxidation. The protective layer may be made of Ti, TiN, Ni, Pt, Au, or the like. The thickness of the protective layer may be as thick as is sufficient to achieve the above-mentioned purpose, and is, for example, 20 to 100 nm. The protective layer may be formed so as to cover not only the top surface of the p-side electrode 17, but also the side surfaces.
[0065] As described above, according to the light-emitting device of embodiment 1, Mg or an Mg alloy is used as the p-side electrode 17 and is in contact with the p-type contact layer 15. Therefore, the contact resistance of the p-side electrode 17 with the p-type contact layer 15 can be reduced and the reflectance of ultraviolet light of the emission wavelength can be increased.
[0066] 2. Light-emitting device manufacturing method Next, a method for manufacturing the light emitting device in embodiment 1 will be described with reference to the drawings.
[0067] First, an n-type layer 11, an active layer 12, an electron blocking layer 13, a compositionally graded layer 14, and a p-type contact layer 15 are laminated in this order on a substrate 10 via a buffer layer by MOCVD (see FIG. 2(a)).
[0068] Next, a predetermined region of the p-type contact layer 15 is dry-etched until it reaches the n-type layer 11 to form a groove (see FIG. 2(b)).
[0069] Next, an n-side electrode 16 is formed by sputtering or vapor deposition on the n-type layer 11 exposed at the bottom of the groove (see FIG. 2(c)).
[0070] Next, annealing is performed in an oxygen-containing atmosphere at a temperature of 500 to 650° C. for 1 to 10 minutes. The oxygen-containing atmosphere is, for example, an atmosphere in which oxygen is mixed with an inert gas such as nitrogen, and the oxygen concentration is, for example, 0.1 to 1 volume %. The annealing is preferably performed under reduced pressure, for example, 1×10 2 ~1×10 4The annealing temperature is preferably 550 to 650°C.
[0071] By performing annealing in an atmosphere containing oxygen, not only can the contact resistance of the n-side electrode 16 be reduced, but also Mg activation treatment of the p-type contact layer 15 can be performed at the same time. This allows the resistance of the p-type contact layer 15 to be reduced and the contact resistance of the n-side electrode 16 with respect to the n-type layer 11 to be reduced at the same time. By performing the annealing simultaneously in this manner, the number of annealing steps is reduced. As a result of reducing the number of annealing steps, deterioration of the electrical characteristics of the light-emitting device can be suppressed.
[0072] The Mg activation treatment of the p-type contact layer 15 and the reduction in contact resistance of the n-side electrode 16 may be performed separately. For example, they may be performed separately by changing the temperature or atmosphere. However, from the viewpoint of thermal damage to the element, it is preferable to perform them simultaneously in a common manner as in the embodiment. When performing them separately, the annealing for reducing the contact resistance of the n-side electrode 16 may be performed in an atmosphere that does not contain oxygen. When performing them separately, for example, the order is the formation of the p-type contact layer 15, annealing for Mg activation, formation of the n-side electrode 16, and annealing of the n-contact.
[0073] Next, the p-side electrode 17 is formed on the p-type contact layer 15 by sputtering or vapor deposition. Here, the p-side electrode 17 is formed to a thickness that functions as a reflective electrode. Specifically, the thickness of the p-side electrode 17 is set so that the reflectance of ultraviolet light of the emission wavelength is 50% or more. In particular, the thickness of the p-side electrode 17 is preferably 40 nm or more, more preferably 80 nm or more.
[0074] Next, annealing is performed in a nitrogen atmosphere at a temperature of 150° C. to 400° C. for 30 seconds to 12 minutes. In this manner, the light emitting device of embodiment 1 is manufactured. The annealing atmosphere is not limited to nitrogen, but may be any inert gas atmosphere. For example, it may be a rare gas such as argon, or a mixed gas of nitrogen and a rare gas. Annealing may be performed at normal pressure, or at reduced pressure. When performing annealing at reduced pressure, for example, 1×10 2 ~1×104 It is Pa.
[0075] The annealing after the formation of the p-side electrode 17 can reduce the forward voltage Vf of the light-emitting element in the embodiment 1 compared to before the annealing. Although the reason for this is not clear, it is considered that the adhesion between the p-type contact layer 15 and the p-side electrode 17 is improved.
[0076] The annealing temperature is more preferably 200° C. or higher and 350° C. or lower. Within this range, Vf can be further reduced compared to before annealing, and the reflectance of the p-side electrode 17 can also be improved compared to before annealing. The annealing temperature is more preferably 250° C. or higher and 330° C. or lower.
[0077] A more preferable annealing time is from 2 minutes to 8 minutes. In this range, Vf can be further reduced compared to before annealing, and the reflectance of the p-side electrode 17 can be improved compared to before annealing. A more preferable annealing time is from 3 minutes to 7 minutes.
[0078] As described above, according to the method for manufacturing the light-emitting element in embodiment 1, after the p-side electrode 17 is formed, annealing is performed under predetermined conditions, so that the Vf of the light-emitting element can be reduced and the reflectance can be further improved.
[0079] 3. Various Experimental Examples Related to the Embodiment Next, various experimental examples according to the first embodiment will be described.
[0080] Experiment 1 A Mg layer was formed on a sapphire substrate, and the back surface of the sapphire substrate (the surface opposite to the Mg layer) was irradiated vertically with ultraviolet light of a wavelength of 280 nm to measure the reflectance. Figure 3 is a graph showing the relationship between the thickness of the Mg layer and the relative reflectance. The relative reflectance is a relative value normalized by taking the reflectance of a 100 nm thick Al layer instead of the Mg layer as 1. For comparison, the relative reflectance of a Ni / Mg layer instead of the Mg layer was also measured. The Ni thickness of the Ni / Mg layer was 3-4 nm, and the Mg thickness was 130 nm.
[0081] As shown in Figure 3, the thicker the Mg layer, the higher the relative reflectance. Furthermore, when the thickness of the Mg layer was 40 nm or more, the relative reflectance of the Mg layer was higher than the relative reflectance of Ni / Mg, which was 0.81. Furthermore, when the thickness of the Mg layer was 80 nm or more, the reflectance was higher than that of the Al layer.
[0082] Experiment 2 A light-emitting device according to the first embodiment was fabricated with each layer configured as described below (hereinafter referred to as the light-emitting device of Example 1). The layer configuration of the light-emitting device is as follows, in order from the p-side electrode 17 side toward the substrate 10 side. The Al composition of the composition gradient layer 14 was continuously decreased from 78% to 72%. p side electrode 17 Mg P-type contact layer 15 Mg-doped GaN, thickness 10 nm Compositionally graded layer 14: Mg-doped AlGaN, thickness 25.5 nm Compositionally graded layer 14: Non-doped AlGaN, thickness 25.5 nm Electron blocking layer 13 Mg-doped AlGaN Al composition 97% Thickness 8.8 nm Electron blocking layer 13 Mg-doped AlN, thickness 8 nm Barrier layer of active layer 12 Si-doped AlGaN Al composition 68% Thickness 2.5 nm Well layer of active layer 12 Non-doped AlGaN Al composition 46% Thickness 1.7 nm Barrier layer of active layer 12 Si-doped AlGaN Al composition 68% Thickness 9.4 nm Hole blocking layer: Non-doped AlN, thickness 0.5 nm Well layer of SL layer Non-doped AlGaN Al composition 46% Thickness 0.5nm Barrier layer of SL layer Si-doped AlGaN Al composition 68% Thickness 50nm n-type layer 11 Si-doped AlGaN Al composition 73% Thickness 35nm n-type layer 11 Si-doped AlGaN Al composition 73% Thickness 150nm n-contact layer Si-doped AlGaN Al composition 73% Thickness 1200nm Regrowth layer: Ga-containing AlN, Al composition 98%, thickness 200 nm AlN template AlN thickness 2900nm Sapphire, thickness 430μm
[0083] For comparison, a light-emitting device in which the p-side electrode 17 was replaced with Ni / Al (hereinafter, the light-emitting device of Comparative Example 1) and a light-emitting device in which the p-side electrode 17 was replaced with Ni / Mg from the Mg layer (hereinafter, the light-emitting device of Comparative Example 2) were fabricated. The light output Po, external quantum efficiency EQE, IV characteristics, and power conversion efficiency WPE were measured for the light-emitting devices of Example 1, Comparative Examples 1, and 2.
[0084] FIG. 4 is a graph showing the current dependency of the optical output Po for the light-emitting elements of Example 1 and Comparative Examples 1 and 2. The optical output Po is a relative value normalized by setting the Po of Comparative Example 1 at a current of 350 mA as 1. As shown in FIG. 4, it was found that the optical output Po of the light-emitting element of Example 1 was improved compared to the light-emitting elements of Comparative Examples 1 and 2. The optical output Po of the light-emitting element of Example 1 was improved by 19.3% compared to the light-emitting element of Comparative Example 1 at a current of 350 mA. The optical output Po of Comparative Example 1 and Comparative Example 2 were approximately the same.
[0085] 5 is a graph showing the current dependency of the external quantum efficiency EQE for the light-emitting devices of Example 1 and Comparative Examples 1 and 2. As shown in FIG. 5, it was found that the external quantum efficiency EQE of the light-emitting device of Example 1 was improved compared to the light-emitting devices of Comparative Examples 1 and 2. The external quantum efficiency EQE of the light-emitting device of Example 1 was improved by 19.7% compared to the light-emitting device of Comparative Example 1 at a current of 350 mA. The external quantum efficiency EQE of Comparative Example 1 and Comparative Example 2 were approximately the same.
[0086] 4 and 5, it is considered that by using Mg for the p-side electrode 17, the reflectance of ultraviolet light is improved, and therefore the light extraction is improved, and the optical output power Po and the external quantum efficiency EQE are improved.
[0087] 6 is a graph showing IV characteristics of the light-emitting elements of Example 1 and Comparative Examples 1 and 2. As shown in FIG. 6, it was found that the light-emitting element of Example 1 had a lower Vf than the light-emitting elements of Comparative Examples 1 and 2. The light-emitting element of Example 1 had a Vf reduced by 5.1% compared to the light-emitting element of Comparative Example 1 at a current of 350 mA. The reason for the lower Vf is thought to be that Mg has better adhesion to the p-type contact layer 15 than Ni / Al or Ni / Mg, resulting in a reduced contact resistance.
[0088] Fig. 7 is a graph showing the power conversion efficiency WPE of the light-emitting elements of Example 1 and Comparative Examples 1 and 2. As shown in Fig. 7, the power conversion efficiency WPE of the light-emitting element of Example 1 was improved compared to the light-emitting elements of Comparative Examples 1 and 2. The power conversion efficiency WPE of the light-emitting element of Example 1 was increased by 25.6% compared to the light-emitting element of Comparative Example 1 at a current of 350 mA.
[0089] Experiment 3 A Mg layer was formed on a sapphire substrate, and ultraviolet light was irradiated vertically from the back surface of the sapphire substrate (the surface opposite to the Mg layer side) to measure the reflectance. The wavelength of the ultraviolet light was changed in the range of 200 to 300 nm. The thickness of the Mg layer was set to 130 nm. Figure 8 is a graph showing the relationship between the wavelength of ultraviolet light and the relative reflectance. For comparison, the relative reflectance was also measured when Ni / Al was provided instead of the Mg layer and when Ni / Mg was provided. The Ni thickness of the Ni / Al was 3 to 4 nm, and the Al thickness was 130 nm. The Ni thickness of the Ni / Mg was 3 to 4 nm, and the Mg thickness was 130 nm. The relative reflectance is a relative value normalized with the reflectance at a wavelength of 280 nm in the case of Ni / Al set to 1.
[0090] As shown in FIG. 8, Mg had a higher reflectance than Ni / Al and Ni / Mg at any wavelength from 200 to 280 nm.
[0091] Experiment 4 For the light-emitting devices of Example 1 and Comparative Examples 1 and 2, a micrograph of the p-side electrode 17 was taken to confirm the adhesion of the p-side electrode 17. FIG. 9 shows micrographs of the p-side electrode 17, where FIG. 9(a) is for Ni / Al, FIG. 9(b) is for Mg, and FIG. 9(c) is for Ni / Mg. As shown in FIG. 9(c), peeling was observed at the element end in the case of Ni / Mg. On the other hand, as shown in FIGS. 9(a) and 9(b), no peeling was observed in the cases of Ni / Al and Mg. Thus, it was found that when Mg was directly formed on the p-type contact layer 15, the adhesion with the p-type contact layer 15 was better than when Mg was formed via Ni. Therefore, it is considered that the reason why Vf can be reduced when the p-side electrode 17 is made of Mg compared to when it is made of Ni / Mg is due to the better adhesion.
[0092] Test 5 The IV characteristics and emission spectrum of the light emitting device of Example 1 were measured in the cases where annealing was performed and not performed after the formation of the p-side electrode 17. The annealing was performed in a nitrogen atmosphere at 300° C. for 6 minutes.
[0093] Figure 10 is a graph showing the IV characteristics before and after annealing. As shown in Figure 10, it was found that annealing reduces Vf. At a current of 350 mA, annealing reduced Vf by 1.2 V.
[0094] Figure 11 is a graph showing the emission spectra before and after annealing. As shown in Figure 11, it was found that the output at 280 nm, which is the peak emission wavelength, was improved.
[0095] Although it is not clear why annealing reduces Vf and improves light output, it is possible that the adhesion between the p-type contact layer 15 and Mg is improved. Of course, other factors are not excluded.
[0096] Test 6 The light emitting device of Example 1 was annealed after the formation of the p-side electrode 17, and the relationship between the annealing temperature and the amount of reduction in Vf was examined. In addition, Mg / Ti was formed on a sapphire substrate, and then annealed, and the relationship between the annealing temperature and the amount of change in reflectance was examined. The annealing was performed in a nitrogen atmosphere for 3 minutes, and the temperature was changed between 250 and 570°C. FIG. 12 is a graph showing the change in the annealing temperature over time. As shown in FIG. 12, the temperature was raised to 150°C about 20 seconds after the start of heating, and then raised to each set temperature after 90 seconds, and the set temperature was maintained for 3 minutes, after which heating was stopped and the temperature was lowered.
[0097] FIG. 13 is a graph showing the relationship between the annealing temperature and the amount of Vf reduction. The amount of Vf reduction indicates how much the Vf after annealing at 350 mA has changed compared to before annealing. As shown in FIG. 13, when the annealing temperature is less than 400°C, the Vf is lower after annealing than before annealing. On the other hand, when the annealing temperature is 400°C, the Vf is higher after annealing than before annealing. Furthermore, when the temperature exceeds 400°C, the light-emitting element breaks down. From the above, it was found that annealing should be performed at 400°C or less, and that the annealing temperature should be less than 400°C in order to reduce the Vf.
[0098] FIG. 14 is a graph showing the relationship between the annealing temperature and the amount of change in reflectance of Mg / Ti. The amount of change in reflectance indicates how much the reflectance after annealing has changed compared to before annealing. The Mg thickness in Mg / Ti was 130 nm, and the Ti thickness was 52 nm. Other conditions were the same as in Experiment 1. As shown in FIG. 14, it was found that if the annealing temperature was 300°C or less, the reflectance after annealing was higher than that before annealing. On the other hand, if the annealing temperature was 350°C or more, the reflectance after annealing was lower than that before annealing. From the above, it was found that the annealing temperature should be less than 350°C in order to improve the reflectance.
[0099] Test 7 The light-emitting device of Example 1 was annealed after the formation of the p-side electrode 17, and the relationship between the annealing time and the amount of Vf reduction was examined. In addition, Mg / Ti was formed on a sapphire substrate, and then annealed, and the relationship between the annealing time and the amount of change in reflectance was examined. The annealing was performed in a nitrogen atmosphere at a temperature of 300°C. The annealing time was changed between 1 minute and 12 minutes. FIG. 15 is a graph showing the change in annealing temperature over time. As shown in FIG. 15, the temperature was raised to 150°C about 20 seconds after the start of heating, and then raised to 300°C after 90 seconds, and 300°C was maintained for each set time, after which heating was stopped and the temperature was lowered.
[0100] FIG. 16 is a graph showing the relationship between annealing time and the amount of Vf reduction. The amount of Vf reduction indicates how much the Vf after annealing at 350 mA has changed compared to before annealing. As shown in FIG. 16, regardless of the annealing time from 1 to 12 minutes, it was found that the Vf after annealing is lower than before annealing. In addition, it was found that the amount of Vf reduction increases with increasing annealing time up to 6 minutes, but when the annealing time exceeds 6 minutes, the amount of Vf reduction saturates and becomes approximately constant. From the above, it was found that an annealing time of 1 minute or more is sufficient to reduce Vf. It is also estimated that the Vf reduction effect is achieved even when the annealing time is in the range of 30 seconds or more and less than 1 minute.
[0101] FIG. 17 is a graph showing the relationship between annealing time and the amount of change in reflectance of Mg / Ti. The amount of change in reflectance indicates how much the reflectance after annealing has changed compared to before annealing. The Mg thickness in Mg / Ti was 130 nm, and the Ti thickness was 52 nm. Other conditions were the same as in Experiment 1. As shown in FIG. 17, it was found that the reflectance was higher after annealing than before annealing, regardless of the annealing time from 1 to 12 minutes. From the above, it was found that an annealing time of 1 minute or more is sufficient to improve the reflectance.
[0102] Test 8 The light output Po and Vf of the light emitting device of Example 1 were compared between the case where the annealing atmosphere was a nitrogen atmosphere and the case where the annealing atmosphere was a mixed gas atmosphere of nitrogen and oxygen after the formation of the n-side electrode 16 and before the formation of the p-side electrode 17. The annealing temperature was 570°C, and the annealing time was 4 minutes. The mixed gas had an oxygen concentration of 0.3% by volume.
[0103] Fig. 18 is a graph showing the relationship between the light output Po and the current of the light-emitting element of Example 1. As shown in Fig. 18, when the annealing atmosphere was a mixed gas of nitrogen and oxygen, the light output Po was improved compared to when only nitrogen was used.
[0104] Fig. 19 is a graph showing the IV characteristics of the light-emitting device of Example 1. As shown in Fig. 19, when the annealing atmosphere was a mixed gas of nitrogen and oxygen, Vf was lower than when only nitrogen was used.
[0105] 18 and 19, it can be seen that by performing annealing with a mixed gas containing oxygen before the formation of the p-side electrode 17, it is possible to simultaneously reduce the contact of the n-side electrode 16 and activate the p-type contact layer 15, thereby improving the light output Po and reducing Vf. [Explanation of symbols]
[0106] 10: Substrate 11:N-type layer 12:Active layer 13: Electron block layer 14: Composition gradient layer 15: p-type contact layer 16:n side electrode 17:p side electrode
Claims
1. A flip-chip type ultraviolet light emitting device having a p-type layer made of a p-type Group III nitride semiconductor and a p-side electrode which is a reflective electrode provided on the p-type layer, The p-side electrode is made of Mg or an alloy mainly composed of Mg, and is in contact with the p-type layer.
2. The light-emitting device according to claim 1 , wherein the p-side electrode has a thickness set so that the reflectance at the emission wavelength is 50% or more.
3. 3. The light-emitting device according to claim 1, wherein the p-side electrode has a thickness of 40 nm or more.
4. The light-emitting device according to claim 3 , wherein the p-side electrode has a thickness of 80 nm or more.
5. The light-emitting device according to claim 1 , further comprising a protective layer made of Ti, TiN or Ni, provided on and in contact with the p-side electrode.
6. 2. The light emitting device according to claim 1, wherein the light emitting device has an emission wavelength of 210 to 280 nm.
7. A method for manufacturing a flip-chip type ultraviolet light-emitting light-emitting device having a p-type layer made of a p-type Group III nitride semiconductor and a p-side electrode which is a reflective electrode provided on the p-type layer, comprising: a p-side electrode formation step of forming the p-side electrode made of Mg or an alloy mainly containing Mg on and in contact with the p-type layer; After the formation of the p-side electrode, an annealing step is performed in an inert gas atmosphere at a temperature of 150° C. to 400° C. for 30 seconds to 12 minutes.
8. The method for manufacturing a light-emitting element according to claim 7 , wherein the annealing temperature in the annealing step is 200° C. or more and 350° C. or less.
9. 9. The method for manufacturing a light-emitting element according to claim 7, wherein an annealing time in the annealing step is from 2 minutes to 8 minutes.
10. The method for manufacturing a light-emitting element according to claim 7 , wherein the p-side electrode forming step forms the p-side electrode to have a thickness of 40 nm or more.
11. The method for manufacturing a light-emitting element according to claim 10 , wherein the p-side electrode forming step forms the p-side electrode to have a thickness of 80 nm or more.
12. 8. The method for manufacturing a light-emitting element according to claim 7, wherein the p-side electrode formation step further comprises the step of forming a protective layer made of Ti, TiN or Ni on and in contact with the p-side electrode.
13. 8. The method for producing a light-emitting element according to claim 7, wherein the light-emitting element has an emission wavelength of 210 to 280 nm.
Citation Information
Patent Citations
Semiconductor element
JP2019036729A
Manufacturing method for nitride semiconductor element
JP2021100032A
Ultraviolet light-emitting element, and light-emitting structure
JP2014096539A
Deep ultraviolet light-emitting diode and electrical equipment with the same
JP2019036629A